Fluctuating formality: homeownership, inheritance and the official economy in urban South Africa - Bolt, M (Wiley, 2021)
One of Malinowski's legacies was a sensitivity to the ways institutions unevenly shape lives and relationships. Taking his lead, this article develops an approach to the formal economy, combining, sharpening, and extending theories of state and market infrastructures in political and economic anthropology. Focusing on urban South Africa, it examines property inheritance among the black majority previously excluded from property rights. As a lens on the formal economy, this moves beyond production to consider how social reproduction – passing on property – weaves through disjointed state processes. The article argues that the formal economy is sustained by particular performances of its scripts: different actors connect fragments of process in their own projects, with little commitment to the official logics that notionally make systems. In a setting where state responsibility over inheritance has expanded, formality's advancing frontiers throw its fluctuating character into relief: institutions’ apparently coherent abstractions are given force in piecemeal fashion.